2018
DOI: 10.1002/hep4.1210
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of Cytochromes in Hepatic Extracellular Vesicles Is Altered by Drugs Related With Drug‐Induced Liver Injury

Abstract: Drug‐induced liver injury (DILI) is a serious worldwide health problem that accounts for more than 50% of acute liver failure. There is a great interest in clinical diagnosis and pharmaceutical industry to elucidate underlying molecular mechanisms and find noninvasive biomarkers for this pathology. Cell‐secreted extracellular vesicles (EVs) have provided a new biological source to identify low disease invasive markers. Despite the intense research developed on these vesicles, there is currently a gap on their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…Furthermore, studies have revealed that EVs carry a multitude of drug metabolizing enzymes, including members of the CYP enzyme group [23,83,84] (Table 2). However, the presence and amount of CYP enzymes is likely to vary greatly depending on the EV source, whether the EVs are isolated from plasma or a specific cell line, as well as the physiological condition of the cells from which they originate [85].…”
Section: Role Of Circulatory Cyps In Drug Metabolism and In Cell-cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, studies have revealed that EVs carry a multitude of drug metabolizing enzymes, including members of the CYP enzyme group [23,83,84] (Table 2). However, the presence and amount of CYP enzymes is likely to vary greatly depending on the EV source, whether the EVs are isolated from plasma or a specific cell line, as well as the physiological condition of the cells from which they originate [85].…”
Section: Role Of Circulatory Cyps In Drug Metabolism and In Cell-cellmentioning
confidence: 99%
“…For example, alcohol use increases CYP2E1 expression in plasma EVs [88] and there is a correlation between increased CYP2E1 level and alcohol-induced liver injury [99]. Furthermore, alcohol exposure increases EV release into the circulation [88], making circulatory EVs a potential source of biomarkers in the setting of drug-induced liver injury [84,100].…”
Section: Circulating Cyp Enzymes As Biological Markers Of Drug-inducementioning
confidence: 99%
“…The presence of cytochromes in rat hepatocytederived EVs was described in vitro [31], but also in vivo, where increasing values of active Cyp2d1 was observed in rats under DILI challenge [55], and interestingly, it has been described that there is an increasing activity of CYP2E1 in circulating EVs isolated from human samples after alcohol exposure [56]. Potentially, circulating active cytochromes could trigger activation of drugs, such as acetaminophen, which could end up in tissue damage, in the same way that liver-produced toxic metabolites are toxic for other tissues [91].…”
Section: Cytochromes P450 (Cyps)mentioning
confidence: 96%
“…Undoubtedly, the successful implementation of Genotyping, Exosome, M&S, and Biomarker (“GEMB”)‐based methods, by minimizing probe drug administration and obviating the need for invasive tissue biopsy, would be a great boon to nonclinical researchers and clinical pharmacologists. Further expansion of GEMB–based approaches with other aspects of clinical testing, such as TOX and pharmacodynamics, could also advance translational PK‐pharmacodynamics‐ADME‐DDI‐TOX science in the service of patients, researchers, and agency reviewers …”
Section: Envisioning the Futurementioning
confidence: 99%